2006
DOI: 10.1677/erc.1.01250
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and antiproliferative effect of molecular iodine in the MCF-7 breast cancer cell line

Abstract: This study analyzes the uptake and antiproliferative effect of two different chemical forms of iodine, iodide (I K ) and molecular iodine (I 2 ), in MCF-7 cells, which are inducible for the Na C =I K symporter (NIS) and positive for pendrin (PDS). The mouse fibroblast cell line NIH3T3 was used as control. Our results show that in MCF-7 cells, IK uptake is sustained and dependent on NIS, whereas I 2 uptake is transient with a maximal peak at 10 min and a final retention of 10% of total uptake. In contrast, no I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
65
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 41 publications
12
65
0
1
Order By: Relevance
“…Our studies in the human tumoral mammary cell line MCF-7 show that I 2 is taken up by a facilitated diffusion system and is then incorporated into iodolipids similar to the 6-IL standard. Our data also show that both I 2 and 6-IL exert antiproliferative and apoptotic properties (Arroyo-Helguera et al 2006b); however, little is known about the molecular mechanisms involved in these effects.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our studies in the human tumoral mammary cell line MCF-7 show that I 2 is taken up by a facilitated diffusion system and is then incorporated into iodolipids similar to the 6-IL standard. Our data also show that both I 2 and 6-IL exert antiproliferative and apoptotic properties (Arroyo-Helguera et al 2006b); however, little is known about the molecular mechanisms involved in these effects.…”
Section: Introductionsupporting
confidence: 64%
“…6-IL was synthesized according to the procedure described previously (Arroyo-Helguera et al 2006b), where its purity was analyzed by reverse-phase HPLC and by ascending thin layer chromatography (TLC) using chloroform:methanol (97.5:2.5%, v/v). The spots were detected using iodine vapors.…”
Section: Synthesis Of 6-ilmentioning
confidence: 99%
“…Several groups have postulated that the antineoplastic I 2 effect could be mediated by direct antioxidant/oxidant action at the mitochondrial level or by the formation of iodolipid intermediates such as 6-IL or iodohexadecanal (Dugrillon et al 1994, Shrivastava et al 2006, Rosner et al 2010. Our group has demonstrated that 6-IL formation in solid tumors (MNU) or cancerous cells (MCF-7) is associated with elevated concentrations of its precursor AA, and that 6-IL formation is independent of peroxidases when the supplement is I 2 (Arroyo- Helguera et al 2006). DMBA tumors were previously reported to contain high concentrations of AA and/or its metabolites (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…During gestation, iodine deficiency is a risk factor of preeclampsia (13)(14)(15)(16)(17). Iodine per se has several functions: bactericidal, apoptosis inducer, antioxidant, and it has been recently involved in migration, invasion and trophoblast differentiation (18)(19)(20)(21)(22). Regarding the role of iodine as an antioxidant, it has been proposed that it can act directly as an electron donor and compete for binding sites with free radicals (23).…”
Section: Introductionmentioning
confidence: 99%